The Role of the Digital Audience in Directing the Traditional Approach of Media Institutions and Their Strategies: BBC as a Model - Hinderen Makki Abdul-Hassan, Rese; Hatef Pourrashidi Ali , Prof. Dr. (lark, 2024)
Digital technologies in the field of media have nourished human curiosity and the desire to obtain information quickly, despite the challenges and economic problems faced by traditional media such as television, newspapers, and radio.This situation has led to a multimedia trend of delivering news visually and audio, as well as through video and news texts, making it easier for the public to access news and communicate with the outside world with less effort. The competition between new and traditional media has become like a race for players to win the largest number of points and attract the largest possible number of followers in light of these circumstances, some media institutions, whether governmental or private, found themselves facing fateful decisions related to the choice between remaining in the second class and being satisfied with the current audience, or moving to the influence of modern media and moving forward
Keywords: Media Institution ,Traditional Digital Audience Approach